Command economy in theory (Economic and Political Thought, 2015)
The article presents a theoretical analysis of a command economy froma historical perspective. Presenting the Soviet system, the author refers to theMarxist-Leninist-Stalinist heritage. This is the spirit of the author’s analysis ofthe system limited by demand or available resources and a discussion of theforms of property and the methods of co-ordination used in the commandsystem as well as the specific system of budget development. At the sametime, the author emphasises that there is a lack of theoretical analyses of thethen used economic system as they were not conducted at that time, and thusthere are no indicators that would make it possible to lay down guidelines onreforming such a system.